Effectiveness of Genetic Module to Reduce Misconception Levels and Improve Cognitive Learning Outcomes of Grade XII Students of SMA Negeri 5 Malang - Didik Dwi Prastyo; Mohamad Amin; Hendra Susanto (Journal of Disruptive Learning Innovation (JODLI), 2021)
We investigate the effectiveness of module to reduce misconception and improve learning outcomes in genetic material using multiple choice test with CRI. This study using pre-experiment study with one group pretest post test design. This study reports the results of analysis of misconception level of XII grades in SMA Negeri 5 Malang reduce from 33.42 percent to 12.92 percent. Learning outcome increase from 38.30 into 72.96.  These results indicate that the genetic module is effective to reducing the level of misconceptions and improving student cognitive learning outcomes.Keywords: Misconception, learning outcomes, genetic